2018
DOI: 10.1111/ijcp.13285
|View full text |Cite
|
Sign up to set email alerts
|

The safety of NOACs in atrial fibrillation patient subgroups: A narrative review

Abstract: Four non-vitamin K oral anticoagulants (NOACs) have been evaluated in clinical trials for the prevention of stroke in patients with atrial fibrillation (AF). Although each of the NOACs have been shown to be at least non-inferior to warfarin for efficacy and safety outcomes, controversy remains over the relative safety of each NOAC in patient subgroups. This narrative review provides an overview of phase III data on NOAC trials for the prevention of stroke in AF, with a focus on reporting the safety of each age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 109 publications
2
6
0
2
Order By: Relevance
“…Consequently, a number of observational, real-world evidence studies have emerged to provide supportive evidence of the safety and/or effectiveness of NOACs in clinical practice 11–18. However, there remain several unmet knowledge gaps in the literature regarding the clinical outcomes of NOAC treatment in patients with NVAF, particularly in patient subgroups at high risk of adverse outcomes 19 20…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of observational, real-world evidence studies have emerged to provide supportive evidence of the safety and/or effectiveness of NOACs in clinical practice 11–18. However, there remain several unmet knowledge gaps in the literature regarding the clinical outcomes of NOAC treatment in patients with NVAF, particularly in patient subgroups at high risk of adverse outcomes 19 20…”
Section: Introductionmentioning
confidence: 99%
“…13 14 Currently, four NOACs, namely, apixaban, dabigatran, edoxaban and rivaroxaban, are licensed for use in the USA and Europe for this indication. 15 The use of NOACs for stroke prevention in NVAF is recommended by several international guidelines, [16][17][18] and is also a well-established clinical practice across the world. 19 It has been reported that NVAF patients who are initiated on oral anticoagulants are increasingly being treated with NOACs when compared with the VKAs.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of thromboembolic complications represents the cornerstone of atrial fibrillation treatment and is based on oral anticoagulation therapy. With the development of NOACs, like dabigatran, rivaroxaban, apixaban, and edoxaban, direct thrombin, or factor X inhibitors, the use of vitamin K antagonists is in decline 11,12 . However, over the last decade, percutaneous closure of left atrial appendage closure (LAAC) proved effective in reducing thromboembolic complications in patients with oral treatment contraindications 13,14 .…”
Section: Discussionmentioning
confidence: 99%